Selective fluorescent sensing and photocatalytic properties of three MOFs based on naphthalene-1, 4-dicarboxylic acid and 2, 4, 5-tri(4-pyridyl)-imidazole. (7th February 2018) - Wang, Jun-Jie; Zhang, Ren-Chun; Cao, Ya-Li; Li, Yan-Ang; Wang, Yi-Ran; Wang, Qing-Lun
Abstract : Three MOFs display high sensitivity in the detection of NB and Ca 2+ or Co 2+ ions as luminescent probes. Moreover, 3 exhibits a relatively good photocatalytic degradation activity of rhodamine B. Abstract : The solvothermal reactions of M II (M = Mn, Zn, Cd) ions with naphthalene-1, 4-dicarboxylic acid (H2 L ) and 2, 4, 5-tri(4-pyridyl)-imidazole (Htpim) gave rise to three MOFs, [Mn(L )0.5 (L )0.5 (Htpim)2 ] n (1 ), [Zn4 (L )4 (Htpim)2 ] n (2 ) and [Cd4 (L )4 (Htpim)2 (DMF)2 ] n (3 ). Single-crystal X-ray diffraction analyses indicate that compounds1–3 display diverse topologies.1 possesses a 2D 4 4 network constructed by linking Mn centers, compound2 exhibits a 3D (3, 4, 6)-connected 4·6 2 2 4 2 ·6 4 2 4 2 ·6 8 ·8 2 ·10 3 net interlinked by [Zn2 L 4 ] units, while compound3 presents a 3D (3, 7)-connected 4 2 ·54 6 ·5 5 ·6 8 ·7 2 framework assembled by dinuclear Cd nodes.1 and3 display high sensitivity in the detection of nitrobenzene (NB) as fluorescent sensors and Ca 2+ or Co 2+ ions as luminescent probes. Moreover, 3 exhibits a relatively good photocatalytic activity towards the degradation of rhodamine B (RhB) in aqueous solution under UV irradiation.